Resin composition
By adding a benzoxazine compound with an alicyclic structure to the resin composition, the problems of warpage inhibition and adhesion improvement in the insulating layer of the printed wiring board are solved, and efficient insulation effect in a high-temperature and low-temperature environment is achieved.
Patent Information
- Application Number
- CN202010142790.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-07
- Filing Date
- 2020-03-04
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-03-04
AI Technical Summary
The prior art is difficult to achieve both warpage suppression and excellent adhesion in the insulating layer of the printed wiring board, especially when a large amount of inorganic filler materials are used.
A benzooxazine compound having one or more alicyclic structures is added to the resin composition to reduce the elastic modulus of the cured product, thereby suppressing warping and improving adhesion.
By reducing the elastic modulus of the cured substance, the suppression of warpage and the improvement of adhesion are achieved, and are suitable for the manufacturing of printed wiring boards in high-temperature and low-temperature environments.
Smart Images

Figure FDA0005245263030000011
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition comprising an epoxy resin and a curing agent; a cured product of the resin composition; a sheet-like laminated material comprising the resin composition; a resin sheet comprising the resin composition; a printed wiring board comprising the cured product; and a semiconductor device comprising the printed wiring board. Background Art
[0002] As a manufacturing technology for printed wiring boards, a manufacturing method based on a build-up method in which insulating layers and conductive layers are alternately stacked is known. In a manufacturing method based on a build-up method, the insulating layer is usually formed by curing a resin composition.
[0003] For printed wiring boards, due to exposure to various environments such as high temperature and low temperature, if the linear thermal expansion coefficient of the cured material used in the insulating layer is high, the insulating layer repeatedly expands and contracts, and cracks are generated due to its deformation. As a method for suppressing the linear thermal expansion coefficient at a low level, a method for combining a large amount of inorganic filler materials in a cured material is known (patent document 1). However, if a large amount of inorganic filler materials are combined in a cured material, the elastic modulus becomes high, and it becomes difficult to suppress warping.
[0004] Furthermore, it has been found that when a large amount of inorganic filler is contained in the cured material, the adhesion between the conductor layer such as copper foil and the insulating layer decreases. Recently, there is a demand for smaller semiconductor chip packages, and therefore, excellent adhesion is required.
[0005] Therefore, even when a relatively large amount of an inorganic filler is used, a cured material is required that can simultaneously achieve suppression of warpage due to a low elastic modulus and excellent adhesion.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent document 1: Japanese Patent Application Publication No. 2016-27097. Summary of the invention
[0009] Problems to be solved by the invention
[0010] An object of the present invention is to provide a resin composition capable of achieving both suppression of warpage of the obtained cured product and excellent adhesion.
[0011] Means for solving problems
[0012] In order to achieve the subject of the present invention, the present inventors conducted intensive studies and found that by including (C) a benzoxazine compound having one or more alicyclic structures in the molecule in the resin composition, the elastic modulus of the cured product can be reduced, thereby achieving both suppression of warping and excellent adhesion, thereby completing the present invention.
[0013] That is, the present invention includes the following contents:
[0014] [1] A resin composition comprising (A) an epoxy resin, (B) an inorganic filler, and (C) a benzoxazine compound having an alicyclic structure in the molecule;
[0015] [2] The resin composition according to [1] above, wherein the alicyclic structure of the component (C) is a cyclohexane ring structure;
[0016] [3] The resin composition according to [1] or [2] above, wherein the component (C) is a compound represented by formula (2).
[0017] [Chemical formula 1]
[0018] .
[0019] 〔In the formula, R 1 and R 2 Each independently represents a substituent, Y represents a chemical bond, an alkylene group having 1 to 6 carbon atoms, -O-, -S-, -SO2-, -NH-, -CO-, -CONH-, -NHCO-, -COO-, or -OCO-, s and t each independently represent an integer of 0 to 4, and u represents 0 or 1.]
[0020] [4] The resin composition according to any one of [1] to [3] above, wherein the content of the component (B) is 50% by mass or more when the total non-volatile components in the resin composition are taken as 100% by mass;
[0021] [5] The resin composition according to any one of [1] to [4] above, wherein the average particle size of component (B) is 10 μm or less;
[0022] [6] The resin composition according to any one of [1] to [5] above, further comprising (D) an elastomer;
[0023] [7] The resin composition according to any one of [1] to [6] above, further comprising (E) a curing agent;
[0024] [8] The resin composition according to any one of [1] to [7] above, which is used to form an insulating layer;
[0025] [9] A cured product, which is a cured product of the resin composition described in any one of [1] to [8] above;
[0026]
[10] A sheet-like laminated material comprising the resin composition described in any one of [1] to [8] above;
[0027]
[11] A resin sheet comprising a support and a resin composition layer formed from the resin composition described in any one of [1] to [8] above and disposed on the support;
[0028]
[12] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition described in any one of [1] to [8] above;
[0029]
[13] A semiconductor device comprising the printed wiring board described in
[12] above.
[0030] Effects of the Invention
[0031] According to the present invention, it is possible to provide a resin composition capable of achieving both suppression of warpage of a cured product and excellent adhesion by reducing the elastic modulus of the cured product. DETAILED DESCRIPTION
[0032] Hereinafter, the present invention will be described in detail according to the preferred embodiments of the present invention. However, the present invention is not limited to the following embodiments and examples, and can be arbitrarily modified and implemented within the scope of the claims of the present invention and their equivalents.
[0033] <Resin composition>
[0034] The resin composition of the present invention comprises (A) an epoxy resin, (B) an inorganic filler, and (C) a benzoxazine compound having an alicyclic structure in the molecule.
[0035] By using such a resin composition, the elastic modulus of the cured product can be reduced, thereby achieving both suppression of warping and excellent adhesion.
[0036] The resin composition of the present invention may contain any component in addition to (A) epoxy resin, (B) inorganic filler, and (C) benzoxazine compound having an alicyclic structure in the molecule. As the arbitrary component, for example, (D) elastomer, (E) curing agent, (F) curing accelerator, (G) organic solvent, and (H) other additives may be cited. Hereinafter, each component contained in the resin composition is described in detail.
[0037] <(A) Epoxy resin>
[0038] The resin composition of the present invention contains (A) an epoxy resin.
[0039] (A) Epoxy resins include, for example, biphenylol epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol AF epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins, glycidylamine epoxy resins, glycidylester epoxy resins, cresol novolac epoxy resins, biphenyl epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane epoxy resins, cyclohexanedimethanol epoxy resins, naphthylene ether epoxy resins, trimethylol epoxy resins, tetraphenylethane epoxy resins, and the like. The epoxy resins may be used alone or in combination of two or more.
[0040] For the resin composition, as (A) epoxy resin, it is preferred to include an epoxy resin having two or more epoxy groups in one molecule. From the viewpoint of significantly obtaining the desired effect of the present invention, relative to 100% by mass of the non-volatile component of the (A) epoxy resin, the proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0041] Epoxy resins include epoxy resins that are liquid at a temperature of 20°C (hereinafter, sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20°C (hereinafter, sometimes referred to as "solid epoxy resins"). In one embodiment, the resin composition of the present invention contains a liquid epoxy resin as the epoxy resin. In one embodiment, the resin composition of the present invention contains a solid epoxy resin as the epoxy resin. The resin composition of the present invention may contain only a liquid epoxy resin as the epoxy resin, or may contain only a solid epoxy resin as the epoxy resin, but preferably contains a liquid epoxy resin and a solid epoxy resin in combination as the epoxy resin.
[0042] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.
[0043] As liquid epoxy resins, preferred are bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexanedimethanol type epoxy resins, glycidyl amine type epoxy resins, and epoxy resins having a butadiene structure.
[0044] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "EPIKOTE 828EL" (bisphenol A-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" (glycidylamine-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ZX1059" (a mixture of bisphenol A-type epoxy resin and bisphenol F-type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemicals; "EX-721" (glycidyl ester-type epoxy resin) manufactured by Nagase ChemteX; and "Celloxide 2021P" (alicyclic epoxy resin with an ester skeleton); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins with butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel & Sumitomo Chemical Co., Ltd., etc. They can be used alone or in combination of two or more.
[0045] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferred.
[0046] As solid epoxy resins, preferred are biphenylol-type epoxy resins, naphthalene-type epoxy resins, naphthalene-type tetrafunctional epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, naphthylene ether-type epoxy resins, anthracene-type epoxy resins, bisphenol A-type epoxy resins, bisphenol AF-type epoxy resins, and tetraphenylethane-type epoxy resins.
[0047] Specific examples of solid epoxy resins include "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation; and "HP-7200HH" manufactured by DIC Corporation. ”, “HP-7200H”, “EXA-7311”, “EXA-7311-G3”, “EXA-7311-G4”, “EXA-7311-G4S”, “HP6000” (naphthylene ether type epoxy resin); “EPPN-502H” (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; “NC7000L” (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; “NC3000H”, “NC3000”, “NC3000” manufactured by Nippon Kayaku Co., Ltd. L", "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthol type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.; "YX4000H", "YX4000", "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX4000HK" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation "YX7700" manufactured by Mitsubishi Chemical Corporation (a novolac epoxy resin containing a xylene structure); "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" manufactured by Mitsubishi Chemical Corporation (a bisphenol AF epoxy resin); "YL7800" manufactured by Mitsubishi Chemical Corporation (a fluorene epoxy resin); "jER1010" manufactured by Mitsubishi Chemical Corporation (a solid bisphenol A epoxy resin); "jER1031S" manufactured by Mitsubishi Chemical Corporation (a tetraphenylethane epoxy resin), etc. These may be used alone or in combination of two or more.
[0048] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin (A), the mass ratio of the liquid epoxy resin to the solid epoxy resin is preferably 1:1 to 1:30, more preferably 1:1 to 1:20, and particularly preferably 1:1 to 1:10. By setting the mass ratio of the liquid epoxy resin to the solid epoxy resin within the above range, the desired effect of the present invention can be significantly obtained.
[0049] The epoxy equivalent of the (A) epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and further more preferably 110 g / eq. to 1000 g / eq. By being within the above range, the crosslinking density of the cured product of the resin sheet becomes sufficient, and an insulating layer with a small surface roughness can be formed. The epoxy equivalent is the mass of a resin containing 1 equivalent of epoxy groups. The epoxy equivalent can be measured in accordance with JIS K7236.
[0050] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the epoxy resin (A) is preferably 100 to 5000, more preferably 250 to 3000, and even more preferably 400 to 1500. The weight average molecular weight of the resin can be measured as a value in terms of polystyrene by gel permeation chromatography (GPC).
[0051] The content of (A) epoxy resin is not particularly limited. When the non-volatile components other than the (B) component in the resin combination are set to 100% by mass, from the viewpoint of significantly obtaining the desired effect of the present invention, it is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and particularly preferably 20% by mass or more. From the viewpoint of significantly obtaining the desired effect of the present invention, its upper limit is preferably 60% by mass or less, more preferably 50% by mass or less, further preferably 40% by mass or less, and particularly preferably 30% by mass or less.
[0052] <(B) Inorganic fillers>
[0053] The resin composition of the present invention contains (B) an inorganic filler.
[0054] (B) The material of the inorganic filler is not particularly limited, and examples thereof include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate, etc., and silica and alumina are particularly preferred. As silica, examples thereof include amorphous silica, fused silica, crystalline silica, synthetic silica, hollow silica, etc. In addition, as silica, spherical silica is preferred. (B) The inorganic filler can be used alone or in combination of two or more.
[0055] Commercially available products of (B) inorganic fillers include, for example, "UFP-30" manufactured by DENKA Chemical Industries, Ltd.; "SP60-05" and "SP507-05" manufactured by Nippon Steel & Sumitomo Metal Materials Corporation; "YC100C", "YA050C", "YA050C-MJE" and "YA010C" manufactured by Admatechs Co., Ltd.; "UFP-30" manufactured by Denki Kagaku Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N" and "Silfil NSS-5N" manufactured by Tokuyama Co., Ltd.; "SC2500SQ", "SO-C4", "SO-C2", "SO-C1" and "A23-SX-C1" manufactured by Admatechs Co., Ltd.; "DAW-03" and "FB-105FD" manufactured by DENKA Corporation, etc.
[0056] (B) The average particle size of the inorganic filler is not particularly limited, preferably 40 μm or less, more preferably 30 μm or less, further preferably 20 μm or less, further preferably 10 μm or less, and particularly preferably 5 μm or less. The lower limit of the average particle size of the inorganic filler is not particularly limited, preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.1 μm or more, further preferably 0.2 μm or more, further preferably 0.3 μm or more, and particularly preferably 0.4 μm or more. The average particle size of the inorganic filler can be measured by a laser diffraction-scattering method based on Mie scattering theory. Specifically, it can be measured in the following manner: using a laser diffraction scattering particle size distribution measuring device, the particle size distribution of the inorganic filler is made on a volume basis, and the median particle size is used as the average particle size. The sample can be measured using a sample obtained by the following method: weigh 100 mg of inorganic filler material and 10 g of methyl ethyl ketone into a vial and disperse it for 10 minutes using ultrasound. For the sample to be measured, a laser diffraction particle size distribution measuring device is used, and the wavelength of the light source used is set to blue and red, and the volume-based particle size distribution of the inorganic filler is measured in a flow cell mode, and the average particle size is calculated as the median particle size from the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" made by Horiba, Ltd., etc. can be cited.
[0057] For (B) inorganic filler, from the viewpoint of improving moisture resistance and dispersibility, it is preferably treated with one or more surface treatment agents such as aminosilane coupling agent, epoxysilane coupling agent, mercaptosilane coupling agent, alkoxysilane compound, organic silazane compound, titanate coupling agent, etc. As commercially available surface treatment agents, for example, Shin-Etsu Chemical Co., Ltd. "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd. "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd. "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd. "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd. "SZ-3 1" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd. "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd. "KBM-4803" (long-chain epoxy type silane coupling agent), Shin-Etsu Chemical Co., Ltd. "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd. "KBM503" (3-methacryloxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd. "KBM5783", etc.
[0058] From the viewpoint of improving the dispersibility of the inorganic filler, it is preferred to control the degree of surface treatment performed by the surface treatment agent within a specified range. Specifically, for 100% by mass of the inorganic filler, it is preferred to perform surface treatment with 0.2% by mass to 5% by mass of the surface treatment agent, more preferably with 0.2% by mass to 3% by mass of the surface treatment agent, and further preferably with 0.3% by mass to 2% by mass of the surface treatment agent.
[0059] The degree of surface treatment by the surface treatment agent can be evaluated by the carbon content per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the carbon content per unit surface area of the inorganic filler is preferably 0.02 mg / m 2 More preferably 0.1 mg / m 2 More preferably, 0.2 mg / m 2 On the other hand, from the viewpoint of preventing the increase of the melt viscosity of the resin composition and the melt viscosity in the sheet form, 1 mg / m 2 Below, more preferably 0.8 mg / m 2 Below, more preferably 0.5 mg / m 2 the following.
[0060] (B) The amount of carbon per unit surface area of the inorganic filler can be measured after washing the surface-treated inorganic filler with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent can be added to the inorganic filler surface-treated with a surface treatment agent, and ultrasonic washing is performed at 25°C for 5 minutes. The supernatant is removed, the solid component is dried, and then the amount of carbon per unit surface area of the inorganic filler is measured using a carbon analyzer. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd. can be used.
[0061] From the viewpoint of further improving the effect of the present invention, the specific surface area of the inorganic filler (B) is preferably 0.01 m 2 / g or more, more preferably 0.1m 2 / g or more, particularly preferably 0.2m 2 There is no particular upper limit, but it is preferably 50 m 2 / g or less, more preferably 20m 2 / g or less, 10m 2 / g or less or 5m 2 The specific surface area of the inorganic filler can be obtained by adsorbing nitrogen on the surface of the sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech) according to the BET method, and calculating the specific surface area by the BET multipoint method.
[0062] (B) The content of inorganic filler is not particularly limited. When all non-volatile components in the resin composition are set to 100% by mass, from the viewpoint of being used for a specific purpose, it is preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, and particularly preferably 70% by mass or more. Generally, there is a tendency for the resin composition containing more inorganic fillers to have a large warping, but for the resin composition of the present invention comprising a combination of (A) to (C) components, even when (B) components are more, warping can be effectively suppressed. On the other hand, the upper limit of the content of (B) inorganic filler is not particularly limited, for example, it can be 98% by mass or less, 95% by mass or less, 90% by mass or less, 85% by mass or less, etc.
[0063] <(C) Benzoxazine compounds having an alicyclic structure in the molecule>
[0064] The resin composition of the present invention contains (C) a benzoxazine compound having an alicyclic structure in the molecule. By using the component (C), the flexibility of the cured product of the resin composition can be improved and the elastic modulus can be reduced. In addition, excellent adhesion can be achieved.
[0065] The "benzoxazine compound" in the (C) component refers to a compound having a 3,4-dihydro-2H-1,3-benzoxazine ring (hereinafter sometimes referred to as a "dihydrobenzoxazine ring"). In the compound, it is preferred to have two or more dihydrobenzoxazine rings in the molecule. In the (C) component, when there are two or more dihydrobenzoxazine rings, the two or more dihydrobenzoxazine rings are preferably bonded from the nitrogen atom of the ring via a connecting group. In the (C) component, it is preferred to have an alicyclic structure in the connecting group. In addition, each dihydrobenzoxazine ring may have a substituent.
[0066] Therefore, the benzoxazine compound (C) having an alicyclic structure in the molecule is preferably a compound represented by formula (1).
[0067] [Chemical formula 2]
[0068] .
[0069] [In the formula, R each independently represents a substituent, X represents an m-valent linking group having an alicyclic structure, m represents an integer of 2 or more, and n represents an integer of 0 to 4].
[0070] In formula (1), the "substituent" of R is not particularly limited as long as it does not hinder the function of component (C), and examples thereof include halogen atoms, cyano groups, amino groups, nitro groups, hydroxyl groups, substituted or unsubstituted alkyl groups, substituted or unsubstituted alkenyl groups, substituted or unsubstituted alkoxy groups, substituted or unsubstituted alkylcarbonyl groups, substituted or unsubstituted aryl groups, substituted or unsubstituted heteroaryl groups, substituted or unsubstituted aryloxy groups, substituted or unsubstituted arylcarbonyl groups, substituted or unsubstituted aralkyl groups, and the like.
[0071] Examples of the "halogen atom" include a fluorine atom, a chlorine atom, and a bromine atom.
[0072] The so-called "alkyl" refers to a linear, branched or cyclic monovalent aliphatic saturated hydrocarbon group. The "alkyl" is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. Examples of the "alkyl" include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, neopentyl, cyclopentyl, cyclohexyl, etc. There are no particular restrictions on the substituent of the alkyl in the "substituted or unsubstituted alkyl", and examples include halogen atoms, cyano, alkoxy, alkylcarbonyl, aryl, heteroaryl, aryloxy, arylcarbonyl, amino, nitro, hydroxyl, etc. The number of substituents is preferably 1 to 3, and more preferably 1.
[0073] The so-called "alkoxy group" refers to a monovalent group (alkyl-O-) formed by an alkyl group bonded to an oxygen atom. The "alkoxy group" is preferably an alkoxy group having 1 to 6 carbon atoms, and more preferably an alkoxy group having 1 to 3 carbon atoms. Examples of the "alkoxy group" include methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy, sec-butoxy, tert-butoxy, pentyloxy, and the like. There are no particular restrictions on the substituent of the alkoxy group in the "substituted or unsubstituted alkoxy group", and examples include halogen atoms, cyano, alkoxy, alkylcarbonyl, aryl, heteroaryl, aryloxy, arylcarbonyl, amino, nitro, hydroxyl, and the like. The number of substituents is preferably 1 to 3, and more preferably 1.
[0074] The so-called "alkenyl" refers to a linear, branched or cyclic monovalent unsaturated hydrocarbon group having at least one carbon-carbon double bond. "Alkenyl" is preferably an alkenyl having 2 to 6 carbon atoms, and more preferably an alkenyl having 2 or 3 carbon atoms. As "alkenyl", for example, vinyl, 1-propenyl, 2-propenyl, 2-methyl-1-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 3-methyl-2-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 4-methyl-3-pentenyl, 1-hexenyl, 3-hexenyl, 5-hexenyl, 2-cyclohexenyl, etc. can be mentioned. As the substituent of the alkenyl in the "substituted or unsubstituted alkenyl", there is no particular limitation, and for example, halogen atoms, cyano groups, alkoxy groups, alkylcarbonyl groups, aryl groups, heteroaryl groups, aryloxy groups, arylcarbonyl groups, amino groups, nitro groups, hydroxyl groups, etc. can be mentioned. The number of substituents is preferably 1 to 3, more preferably 1.
[0075] The so-called "alkylcarbonyl" refers to a monovalent group (alkyl-CO-) formed by an alkyl group bonded to a carbonyl group. The "alkylcarbonyl" is preferably an alkylcarbonyl group having 2 to 7 carbon atoms, and more preferably an alkylcarbonyl group having 2 to 4 carbon atoms. Examples of the "alkylcarbonyl" include acetyl, propionyl, butyryl, 2-methylpropionyl, valeryl, 3-methylbutyryl, 2-methylbutyryl, 2,2-dimethylpropionyl, hexanoyl, heptanoyl, and the like. There are no particular restrictions on the substituent of the alkylcarbonyl in the "substituted or unsubstituted alkylcarbonyl", and examples thereof include halogen atoms, cyano, alkoxy, alkylcarbonyl, aryl, heteroaryl, aryloxy, arylcarbonyl, amino, nitro, hydroxyl, and the like. The number of substituents is preferably 1 to 3, and more preferably 1.
[0076] The so-called "aryl group" refers to a monovalent aromatic hydrocarbon group. The "aryl group" is preferably an aryl group having 6 to 14 carbon atoms, and more preferably an aryl group having 6 to 10 carbon atoms. Examples of the "aryl group" include phenyl, 1-naphthyl, 2-naphthyl, etc., and preferably phenyl. There are no particular restrictions on the substituent of the aryl group in the "substituted or unsubstituted aryl group", and examples include halogen atoms, cyano groups, alkyl groups, alkoxy groups, alkylcarbonyl groups, aryl groups, heteroaryl groups, aryloxy groups, arylcarbonyl groups, aralkyl groups, amino groups, nitro groups, hydroxyl groups, etc. The number of substituents is preferably 1 to 3, and more preferably 1.
[0077] The term "heteroaryl" refers to a monovalent aromatic heterocyclic group having, as ring-constituting atoms, 1 to 4 heteroatoms selected from oxygen atoms, nitrogen atoms and sulfur atoms in addition to carbon atoms. The "heteroaryl" is preferably a 5- to 12-membered (preferably 5- or 6-membered) monocyclic, bicyclic or tricyclic (preferably monocyclic) aromatic heterocyclic group. Examples of the “heteroaryl group” include furanyl, thienyl, pyrrolyl, oxazolyl, isoxazolyl, thiazolyl, isothiazolyl, imidazolyl, pyrazolyl, 1,2,3-oxadiazolyl, 1,2,4-oxadiazolyl, 1,3,4-oxadiazolyl, furazanyl, 1,2,3-thiadiazolyl, 1,2,4-thiadiazolyl, 1,3,4-thiadiazolyl, 1,2,3-triazolyl, 1,2,4-triazolyl, tetrazolyl, pyridyl, pyridazinyl, pyrimidinyl, pyrazinyl, triazinyl, etc. There are no particular restrictions on the substituent of the heteroaryl group in the “substituted or unsubstituted heteroaryl group”, and examples thereof include a halogen atom, cyano, alkyl, alkoxy, alkylcarbonyl, aryl, heteroaryl, aryloxy, arylcarbonyl, aralkyl, amino, nitro, hydroxyl, etc. The number of substituents is preferably 1 to 3, more preferably 1.
[0078] The so-called "aryloxy" refers to a monovalent group formed by an aryl group bonded to an oxygen atom (aryl-O-). The "aryloxy" is preferably an aryloxy group having 6 to 14 carbon atoms, and more preferably an aryloxy group having 6 to 10 carbon atoms. Examples of the "aryloxy" include phenoxy and naphthoxy. There are no particular restrictions on the substituent of the aryloxy in the "substituted or unsubstituted aryloxy", and examples include halogen atoms, cyano, alkyl, alkoxy, alkylcarbonyl, aryl, heteroaryl, aryloxy, arylcarbonyl, aralkyl, amino, nitro, hydroxyl, and the like. The number of substituents is preferably 1 to 3, and more preferably 1.
[0079] The so-called "arylcarbonyl" refers to a monovalent group (aryl-CO-) formed by bonding an aryl group to a carbonyl group. The "arylcarbonyl" is preferably an arylcarbonyl having 7 to 15 carbon atoms, and more preferably an arylcarbonyl having 7 to 11 carbon atoms. Examples of the "arylcarbonyl" include benzoyl, 1-naphthoyl, 2-naphthoyl, and the like. There are no particular restrictions on the substituent of the arylcarbonyl in the "substituted or unsubstituted arylcarbonyl", and examples thereof include a halogen atom, a cyano group, an alkyl group, an alkoxy group, an alkylcarbonyl group, an aryl group, a heteroaryl group, an aryloxy group, an arylcarbonyl group, an aralkyl group, an amino group, a nitro group, a hydroxyl group, and the like. The number of substituents is preferably 1 to 3, and more preferably 1.
[0080] The so-called "aralkyl" refers to an alkyl group substituted with one or more aryl groups. The "aralkyl" is preferably an aralkyl group having 7 to 15 carbon atoms, and more preferably an aralkyl group having 7 to 11 carbon atoms. Examples of the "aralkyl" include benzyl, phenethyl, 2-naphthylmethyl, etc. There are no particular restrictions on the substituent of the aralkyl in the "substituted or unsubstituted aralkyl", and examples include halogen atoms, cyano, alkyl, alkoxy, alkylcarbonyl, aryl, heteroaryl, aryloxy, arylcarbonyl, aralkyl, amino, nitro, hydroxyl, etc. The number of substituents is preferably 1 to 3, and more preferably 1.
[0081] In formula (1), n represents an integer of 0 to 4, preferably 0 or 1, and more preferably 0. That is, the dihydrobenzoxazine ring is more preferably unsubstituted.
[0082] In formula (1), the "m-valent connecting group having an alicyclic structure" of X is not particularly limited, as long as it has at least one alicyclic structure. The number of alicyclic structures in component (C) is not particularly limited, and is preferably 1 to 5, more preferably 1 to 3, and further preferably 1 or 2. Examples of the ring structure of the alicyclic structure in component (C) include cycloalkane rings, cycloolefin rings, and aliphatic heterocycles obtained by replacing at least one of their skeletal carbon atoms with a heteroatom-containing group selected from -O-, -S-, -SO2-, -NH-, -CO-, -CONH-, -NHCO-, -COO-, and -OCO-, among which cycloalkane rings are preferred.
[0083] The so-called "cycloalkane ring" refers to a monocyclic or polycyclic saturated aliphatic hydrocarbon ring. The "cycloalkane ring" is preferably a cycloalkane ring having 3 to 10 carbon atoms. Examples of the "cycloalkane ring" include monocyclic alkane rings such as cyclobutane ring, cyclopentane ring, cyclohexane ring, cycloheptane ring, and cyclooctane ring; bicyclic alkane rings such as decahydronaphthalene ring and norbornane ring; and spiroalkane rings such as spirononane ring.
[0084] The so-called "cycloolefin ring" refers to a monocyclic or polycyclic aliphatic saturated hydrocarbon ring having at least one carbon-carbon double bond. The "cycloolefin ring" is preferably a cycloolefin ring having 3 to 10 carbon atoms. Examples of the "cycloalkane ring" include monocyclic olefin rings such as cyclobutene ring, cyclopropylene ring, cyclohexene ring, cyclohexadiene ring, cycloheptene ring, and cyclooctene ring; bicyclic olefin rings such as norbornene ring and norbornadiene ring; spiroolefin rings such as spirononene ring, etc.
[0085] The number of backbone atoms of the "m-valent linking group having an alicyclic structure" is preferably 3 to 200, more preferably 3 to 100, further preferably 3 to 50, particularly preferably 3 to 20. The backbone atoms may be atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, and sulfur atoms.
[0086] The "m-valent connecting group having an alicyclic structure" of X in formula (1) is preferably a substituted or unsubstituted m-valent saturated aliphatic group containing a ring. Here, as the substituent of the saturated aliphatic group containing a ring in the "substituted or unsubstituted m-valent saturated aliphatic group containing a ring", the same groups as the substituents of R can be cited, preferably unsubstituted. The "saturated aliphatic group containing a ring" includes: a saturated hydrocarbon group containing at least one cycloalkane ring (hereinafter referred to as "saturated hydrocarbon group containing a ring"); and a group obtained by replacing at least one of its skeleton carbon atoms with a heteroatom-containing group selected from -O-, -S-, -SO2-, -NH-, -CO-, -CONH-, -NHCO-, -COO-, and -OCO- (hereinafter referred to as "heteroatom-substituted group of saturated hydrocarbon containing a ring").
[0087] In formula (1), m represents an integer greater than 2, preferably 2 or 3, and more preferably 2. Therefore, in a more preferred embodiment in which m is 2, X is preferably a substituted or unsubstituted divalent saturated aliphatic group containing a ring. The atoms at both ends of the "divalent saturated aliphatic group containing a ring" are preferably arbitrary carbon atoms, and more preferably carbon atoms constituting a ring.
[0088] Specific examples of the "divalent ring-containing saturated aliphatic group" in X of formula (1) include -cHex-, -cPent-, -DECAL-, -NORBOR-, -cHex-cHex-, -cPent-cPent-, -cHex-CH2-cHex-, -cPent-CH2-cPent-, -cHex-CH2-CH2-cHex-, -cPent-CH2-CH2-cPent-, -cHex-CH2-CH2-cHex-, -cPent-CH2-CH2-cPent-, -cHex-CH2-CH2-CH2-cHex-, -cPent-CH2-CH2-cPent-, -cHex-CH2-CH2-CH2-cHex-, -cPent-CH2-CH2-cPent-, -cHex-CH2-CH2-CH2-cHex-, -cPent-CH2-CH2-CH2-cPent-, -c ent-CH2-CH2-CH2-cPent-, -cHex-CH(CH3)-cHex-, -cPent-CH(CH3)-cPent-, -cHex-CH(CH2CH3)-cHex-, -cPent-CH(CH 2CH3)-cPent-, -cHex-C(CH3)2-cHex-, -cPent-C(CH3)2-cPent-, -cHex-C(CH2CH3)2-cHex-, -cPent-C(CH2CH3)2-cPen t-, etc.; -cHex-O-cHex-, -cPent-O-cPent-, -cHex-O-CH2-CH2-O-cHex-, -cPent-O-CH2-CH2-O-cPent-, -cHex-S-cHex-, -cPent-S-cPent-, -cHex-S-CH2-CH2-S-cHex-, -cPent-S-CH2-CH2-S-cPent-, -cHex-CO-cHex-, -cPent-CO -cPent-, -cHex-SO2-cHex-, -cPent-SO2-cPent-, -cHex-CONH-cHex-, -cPent-CONH-cPent-, -cHex-NHCO-cHex-, -cPent-NHCO-cPent-, -cHex-COO-cHex-, -cPent-COO-cPent-, -cHex-OCO-cHex-, -cPent-OCO-cPent-, etc., a divalent ring-containing saturated hydrocarbon heteroatom substituent. Here, "cHex" represents 1,4-cyclohexylene, 1,3-cyclohexylene, or 1,2-cyclohexylene. "cPent" represents 1,3-cyclopentylene and 1,2-cyclopentylene. "DECAL" represents a divalent decahydronaphthyl group, and examples thereof include 2,6-bicyclo[4.4.0]decanylene and 2,7-bicyclo[4.4.0]decanylene. "NORBOR" represents a divalent norbornyl group, and examples thereof include 2,5-bicyclo[2.2.1]heptylene and 2,6-bicyclo[2.2.1]heptylene.
[0089] The alicyclic structure of the (C) component is preferably a cyclohexane ring structure. That is, the (C) component preferably has one or more cyclohexane ring structures in the molecule. The cyclohexane ring structure can be a part of a bicycloalkane ring structure. In this case, preferred examples of the "divalent saturated aliphatic group containing a ring" in X of formula (1) include -cHex-, -DECAL-, -NORBOR-, -cHex-cHex-, -cHex-CH2-cHex-, -cHex-CH2-CH2-cHex-, -cHex-CH2-CH2-CH2-cHex-, -cHex-CH(CH3)-cHex-, -cHex-CH(CH2CH3)-cHex-, -cHex-C(CH3)2-cHex-, -cHex-C(CH2CH 3) a divalent ring-containing saturated hydrocarbon group such as 2-cHex-; a divalent ring-containing saturated hydrocarbon heteroatom substituent group such as -cHex-O-cHex-, -cHex-O-CH2-CH2-O-cHex-, -cHex-S-cHex-, -cHex-S-CH2-CH2-S-cHex-, -cHex-CO-cHex-, -cHex-SO2-cHex-, -cHex-CONH-cHex-, -cHex-NHCO-cHex-, -cHex-COO-cHex-, -cHex-OCO-cHex-.
[0090] (C) The benzoxazine compound having an alicyclic structure in the molecule is particularly preferably a compound represented by formula (2).
[0091] [Chemical formula 3]
[0092] .
[0093] 〔In the formula, R 1 and R 2 Each independently represents a substituent, Y represents a chemical bond, an alkylene group having 1 to 6 carbon atoms, -O-, -S-, -SO2-, -NH-, -CO-, -CONH-, -NHCO-, -COO-, or -OCO-, s and t each independently represent an integer of 0 to 4, and u represents 0 or 1.]
[0094] R 1 and R 2 The "substituent" of is the same as the substituent of R in formula (1). s and t are each independently preferably 0 or 1, and particularly preferably 0.
[0095] The so-called "alkylene group" refers to a straight-chain, branched or cyclic divalent aliphatic saturated hydrocarbon group. The number of carbon atoms of the "alkylene group having 1 to 6 carbon atoms" is preferably 1 to 3. Examples of the "alkylene group having 1 to 6 carbon atoms" include -CH2-, -CH2-CH2-, -CH(CH3)-, -CH2-CH2-CH2-, -CH2-CH(CH3)-, -CH(CH3)-CH2-, -C(CH3)2-, -CH2-CH2-CH2-CH2-, -CH2-CH2-CH(CH3)-, -CH2-CH(CH3)-CH2-, -CH2-CH(CH3)-CH2-, -CH(CH3)-CH2-, -CH2-C(CH3)2-, -C(CH3)2-CH2-, -cHex-, etc.
[0096] Specific examples of the benzoxazine compound (C) having an alicyclic structure in the molecule include 1,4-bis(3,4-dihydro-2H-1,3-benzoxazin-3-yl)cyclohexane, bis[4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)cyclohexyl]methane, 1,2-bis[4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)cyclohexyl]ethane, 2,2-bis[4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)cyclohexyl]propane, bis[4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)cyclohexyl]ether, and bis[4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)cyclohexyl]sulfone.
[0097] The molecular weight of the component (C) is not particularly limited, but is preferably 5,000 or less, more preferably 3,000 or less, further preferably 2,000 or less, and particularly preferably 1,000 or less from the viewpoint of significantly obtaining the desired effects of the present invention.
[0098] The content of the benzoxazine compound (C) having an alicyclic structure in the molecule is not particularly limited. When the non-volatile components other than the component (B) in the resin composition are set to 100% by mass, from the viewpoint of significantly obtaining the desired effect of the present invention, it is preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 3% by mass or more, and particularly preferably 5% by mass or more. From the viewpoint of significantly obtaining the desired effect of the present invention, the upper limit is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 10% by mass or less, and particularly preferably 8% by mass or less.
[0099] <(D) Elastomer>
[0100] The resin composition of the present invention may contain (D) an elastomer as an optional component. By using the (D) elastomer, the flexibility of the cured product of the resin composition can be improved and the elastic modulus can be reduced.
[0101] In the present invention, (D) elastomer refers to a flexible resin, an amorphous resin component dissolved in an organic solvent, preferably a resin having rubber elasticity or a resin polymerized with other components to exhibit rubber elasticity. Examples of rubber elasticity include resins that exhibit an elastic modulus of 1 GPa or less when subjected to a tensile test at 25° C. and 40% RH according to Japanese Industrial Standards (JIS K7161).
[0102] In one embodiment, the component (D) is preferably a resin having one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule. From the viewpoint of obtaining a flexible material, a resin having one or more structures selected from the group consisting of a polybutadiene structure and a polycarbonate structure is more preferred. It should be noted that the so-called "(meth)acrylate" refers to methacrylate and acrylate.
[0103] In another embodiment, component (D) is preferably one or more selected from a resin having a glass transition temperature (Tg) of 25°C or less and a resin that is liquid at 25°C or less. The glass transition temperature of the resin having a glass transition temperature (Tg) of 25°C or less is preferably 20°C or less, and more preferably 15°C or less. The lower limit of the glass transition temperature is not particularly limited, and may generally be -15°C or more. In addition, as a resin that is liquid at 25°C, a resin that is liquid at 20°C or less is preferably a resin that is liquid at 15°C or less, and more preferably a resin that is liquid at 15°C or less.
[0104] As a more preferred embodiment, component (D) is one or more selected from resins having a glass transition temperature of 25°C or less and being liquid at 25°C, and having in the molecule one or more structures selected from the group consisting of a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure.
[0105] The polybutadiene structure includes not only a structure formed by polymerizing butadiene, but also a structure formed by hydrogenating the structure. In addition, for the butadiene structure, only a part of it may be hydrogenated, or all of it may be hydrogenated. In addition, the polybutadiene structure may be included in the main chain or in the side chain in the (D) component.
[0106] As preferred examples of polybutadiene resins, resins containing hydrogenated polybutadiene skeletons, polybutadiene resins containing hydroxyl groups, polybutadiene resins containing phenolic hydroxyl groups, polybutadiene resins containing carboxyl groups, polybutadiene resins containing acid anhydride groups, polybutadiene resins containing epoxy groups, polybutadiene resins containing isocyanate groups, polybutadiene resins containing carbamate groups, etc. can be cited. Among them, polybutadiene resins containing phenolic hydroxyl groups are more preferred. Here, the so-called "resin containing hydrogenated polybutadiene skeleton" refers to a resin in which at least a part of the polybutadiene skeleton is hydrogenated, and it is not necessarily a resin in which the polybutadiene skeleton is completely hydrogenated. As resins containing hydrogenated polybutadiene skeletons, for example, epoxy resins containing hydrogenated polybutadiene skeletons can be cited. In addition, as polybutadiene resins containing phenolic hydroxyl groups, resins having a polybutadiene structure and having phenolic hydroxyl groups can be cited.
[0107] Specific examples of the polybutadiene resin having a polybutadiene structure in the molecule include "Ricon 657" (epoxy-containing polybutadiene), "Ricon 130MA8", "Ricon 130MA13", "Ricon 130MA20", "Ricon 131MA5", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", "Ricon 131MA51", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", "Ricon 131MA52", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", "Ricon 131MA51", "Ricon 131MA10", "Ricon 131MA17", "Ricon 131MA20", "Ricon 131MA 184MA6" (polybutadiene containing anhydride groups), "GQ-1000" (polybutadiene into which hydroxyl groups and carboxyl groups are introduced), "G-1000", "G-2000", "G-3000" (polybutadiene having hydroxyl groups at both ends), "GI-1000", "GI-2000", "GI-3000" (hydrogenated polybutadiene having hydroxyl groups at both ends), "PB3600", "PB4700" (polybutadiene skeleton epoxy compounds) manufactured by Daicel Corporation, "Epofriend A1005", "Epofriend A1010", "Epofriend A1020" (epoxy compounds of block copolymers of styrene, butadiene and styrene), "FCA-061L" (hydrogenated polybutadiene skeleton epoxy compound) manufactured by Nagase ChemteX Co., Ltd., "R-45EPT" (polybutadiene skeleton epoxy compound), etc.
[0108] In addition, as an example of a preferred polybutadiene resin, a linear polyimide (polyimide described in Japanese Unexamined Patent Publication No. 2006-37083 and International Publication No. 2008 / 153208) made of hydroxyl-terminated polybutadiene, a diisocyanate compound and a polyacid or its anhydride can also be cited. The content of the polybutadiene structure of the polyimide resin is preferably 60% to 95% by mass, and more preferably 75% to 85% by mass. The details of the polyimide resin can be referred to the records of Japanese Unexamined Patent Publication No. 2006-37083 and International Publication No. 2008 / 153208, and the contents are incorporated into this specification.
[0109] The number average molecular weight of the hydroxyl-terminated polybutadiene is preferably 500 to 5,000, more preferably 1,000 to 3,000. The hydroxyl equivalent of the hydroxyl-terminated polybutadiene is preferably 250 to 1,250.
[0110] Examples of the diisocyanate compound include aromatic diisocyanates such as toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, xylylene diisocyanate, and diphenylmethane diisocyanate; aliphatic diisocyanates such as hexamethylene diisocyanate; and alicyclic diisocyanates such as isophorone diisocyanate. Among these, aromatic diisocyanates are preferred, and toluene-2,4-diisocyanate is more preferred.
[0111] Examples of the polybasic acid or its anhydride include ethylene glycol ditrimellitate, pyromellitic acid, benzophenonetetracarboxylic acid, biphenyltetracarboxylic acid, naphthalenetetracarboxylic acid, 5-(2,5-dioxotetrahydrofuranyl)-3-methyl-cyclohexene-1,2-dicarboxylic acid, 3,3'-4,4'-diphenylsulfonetetracarboxylic acid and tetrabasic acids and their anhydrides, trimellitic acid, cyclohexanetricarboxylic acid and other tribasic acids and their anhydrides, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho(1,2-C)furan-1,3-dione and the like.
[0112] In addition, the resin having a polybutadiene structure may include a polystyrene structure having a structure obtained by polymerizing styrene.
[0113] Specific examples of polystyrene resins having a polystyrene structure in the molecule include styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-ethylene-ethylene-propylene-styrene block copolymers (SEEPS), styrene-butadiene-butylene-styrene block copolymers (SBBS), styrene-butadiene diblock copolymers, hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-isoprene block copolymers, hydrogenated styrene-butadiene random copolymers, and the like.
[0114] The polystyrene resin may be a commercially available product, for example, hydrogenated styrene-based thermoplastic elastomers "H1041", "Tuftec H1043", "Tuftec P2000", "Tuftec MP10" (manufactured by Asahi Kasei Corporation); epoxidized styrene-butadiene thermoplastic elastomers "Epofriend AT501", "CT310" (manufactured by Daicel Corporation); modified styrene-based elastomers "SEPTON HG252" (manufactured by Kuraray Corporation) having hydroxyl groups; modified styrene-based elastomers "Tuftec N503M" having carboxyl groups, modified styrene-based elastomers "Tuftec N501" having amino groups, and modified styrene-based elastomers "Tuftec M1913" having acid anhydride groups (manufactured by Asahi Kasei Chemicals Corporation); unmodified styrene-based elastomers "SEPTON S8104" (manufactured by Kuraray Corporation), etc. Component (C) may be used alone or in combination of two or more.
[0115] The polysiloxane structure is a structure including a siloxane bond, and is included in, for example, silicone rubber. The polysiloxane structure may be included in the main chain or in the side chain in the component (D).
[0116] Specific examples of the polysiloxane resin having a polysiloxane structure in the molecule include "SMP-2006", "SMP-2003PGMEA", "SMP-5005PGMEA" manufactured by Shin-Etsu Silicone Co., Ltd., and linear polyimide made of amino-terminated polysiloxane and tetrabasic acid anhydride as raw materials (International Publication No. 2010 / 053185).
[0117] The poly(meth)acrylate structure is a structure formed by polymerizing acrylic acid or acrylic acid ester, and also includes a structure formed by polymerizing methacrylic acid or methacrylic acid ester. The (meth)acrylate structure may be contained in the main chain or in the side chain in the component (D).
[0118] Preferred examples of the poly(meth)acrylate resin as a resin having a poly(meth)acrylate structure in the molecule include poly(meth)acrylate resins containing hydroxyl groups, poly(meth)acrylate resins containing phenolic hydroxyl groups, poly(meth)acrylate resins containing carboxyl groups, poly(meth)acrylate resins containing acid anhydride groups, poly(meth)acrylate resins containing epoxy groups, poly(meth)acrylate resins containing isocyanate groups, poly(meth)acrylate resins containing urethane groups, and the like.
[0119] Specific examples of poly(meth)acrylate resins include TEISANRESIN "SG-70L", "SG-708-6", "WS-023", "SG-700AS", "SG-280TEA" (carboxyl-containing acrylate copolymer resins, acid values of 5 to 34 mgKOH / g, weight average molecular weights of 400,000 to 900,000, Tg of -30°C to 5°C), "SG-80H", "SG-80H-3", "SG-P3" (epoxy-containing acrylate copolymer resins, epoxy equivalents of 4761 to 14285 g / eq, weight average molecular weight of 350,000) manufactured by Nagase ChemteX Co., Ltd. ~850,000, Tg is 11°C~12°C), "SG-600TEA", "SG-790" (hydroxyl-containing acrylate copolymer resin, hydroxyl value is 20~40mgKOH / g, weight average molecular weight is 500,000~1.2 million, Tg is -37°C~-32°C), "ME-2000", "W-116.3" (carboxyl-containing acrylate copolymer resin), "W-197C" (hydroxyl-containing acrylate copolymer resin), "KG-25", "KG-3000" (epoxy-containing acrylate copolymer resin) made by Negami Industries, Ltd., etc.
[0120] The polyalkylene structure preferably has a predetermined number of carbon atoms. The specific number of carbon atoms in the polyalkylene structure is preferably 2 or more, more preferably 3 or more, particularly preferably 5 or more, preferably 15 or less, more preferably 10 or less, particularly preferably 6 or less. In addition, the polyalkylene structure may be included in the main chain or in the side chain in the component (D).
[0121] The polyalkyleneoxy structure preferably has a predetermined number of carbon atoms. The specific number of carbon atoms in the polyalkyleneoxy structure is preferably 2 or more, preferably 3 or more, more preferably 5 or more, preferably 15 or less, more preferably 10 or less, and particularly preferably 6 or less. The polyalkyleneoxy structure may be contained in the main chain or in the side chain in the component (D).
[0122] Specific examples of polyalkylene resins having a polyalkylene structure in the molecule and polyalkyleneoxy resins having a polyalkyleneoxy structure in the molecule include "PTXG-1000" and "PTXG-1800" manufactured by Asahi Kasei Fibers Corporation, "YX-7180" (a resin containing an alkylene structure having an ether bond) manufactured by Mitsubishi Chemical Corporation, "EXA-4850-150", "EXA-4816" and "EXA-4822" manufactured by DIC Corporation, "EP-4000", "EP-4003", "EP-4010" and "EP-4011" manufactured by ADEKA Corporation, "BEO-60E" and "BPO-20E" manufactured by Shin Nippon Rika Co., Ltd., and "YL7175" and "YL7410" manufactured by Mitsubishi Chemical Corporation.
[0123] The polyisoprene structure may be contained in the main chain or in the side chain of the component (D). Specific examples of the polyisoprene resin having a polyisoprene structure in the molecule include "KL-610" and "KL-613" manufactured by Kuraray Co., Ltd.
[0124] The polyisobutylene structure may be contained in the main chain or in the side chain in the component (D). Specific examples of the polyisobutylene resin having a polyisobutylene structure in the molecule include "SIBSTAR-073T" (styrene-isobutylene-styrene triblock copolymer) and "SIBSTAR-042D" (styrene-isobutylene diblock copolymer) manufactured by KANEKA Corporation.
[0125] The polycarbonate structure may be contained in the main chain or in the side chain in the component (D).
[0126] Preferred examples of polycarbonate resins as resins having a polycarbonate structure in the molecule include hydroxyl group-containing polycarbonate resins, phenolic hydroxyl group-containing polycarbonate resins, carboxyl group-containing polycarbonate resins, acid anhydride group-containing polycarbonate resins, epoxy group-containing polycarbonate resins, isocyanate group-containing polycarbonate resins, and urethane group-containing polycarbonate resins.
[0127] Specific examples of the polycarbonate resin include "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090" and "C-3090" (polycarbonate diol) manufactured by Kuraray Corporation.
[0128] In addition, as an example of a preferred polycarbonate resin, a linear polyimide made of a hydroxyl-terminated polycarbonate, a diisocyanate compound, and a polyacid or its anhydride as a raw material can also be cited. The linear polyimide has a carbamate structure and a polycarbonate structure. The content of the polycarbonate structure of the polyimide resin is preferably 60% to 95% by mass, and more preferably 75% to 85% by mass. The details of the polyimide resin can be referred to the record of International Publication No. 2016 / 129541, and the content is incorporated into this specification.
[0129] The number average molecular weight of the hydroxyl-terminated polycarbonate is preferably 500 to 5,000, more preferably 1,000 to 3,000. The hydroxyl equivalent of the hydroxyl-terminated polycarbonate is preferably 250 to 1,250.
[0130] The component (D) preferably further has an imide structure. The imide structure can improve the heat resistance of the component (D) and effectively improve the crack resistance.
[0131] The component (D) may have any structure of a linear chain, a branched chain, or a cyclic structure, but is preferably a linear chain.
[0132] The component (D) preferably has a functional group that can react with the component (A). The functional group also includes a reactive group that appears by heating. By providing the component (D) with a functional group, the mechanical strength of the cured product of the resin composition can be improved.
[0133] As the functional group, there can be mentioned a carboxyl group, a hydroxyl group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a carbamate group, etc. Among them, from the viewpoint of significantly obtaining the effect of the present invention, as the functional group, it is preferred to have one or more functional groups selected from a hydroxyl group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a carbamate group, and it is particularly preferred to have a phenolic hydroxyl group.
[0134] The component (D) may be used alone or in combination of two or more.
[0135] From the viewpoint of exerting flexibility, component (D) is preferably a high molecular weight. The specific number average molecular weight Mn of component (D) is preferably 4000 or more, more preferably 4500 or more, further preferably 5000 or more, particularly preferably 5500 or more, preferably 100000 or less, more preferably 95000 or less, particularly preferably 90000 or less. The number average molecular weight Mn of component (D) is the number average molecular weight measured by GPC (gel permeation chromatography) in terms of polystyrene conversion.
[0136] From the viewpoint of obtaining flexibility, the specific weight average molecular weight of the component (D) is preferably 5500 to 100000, more preferably 10000 to 90000, and even more preferably 15000 to 80000. The weight average molecular weight of the component (D) is a weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC).
[0137] When the component (D) has a functional group, the functional group equivalent of the component (D) is preferably 100 g / eq. or more, more preferably 200 g / eq. or more, further preferably 1000 g / eq. or more, particularly preferably 2500 g / eq. or more, preferably 50000 g / eq. or less, more preferably 30000 g / eq. or less, further preferably 10000 g / eq. or less, particularly preferably 5000 g / eq. or less. The functional group equivalent is the number of grams of the resin containing 1 gram equivalent of the functional group. For example, the epoxy equivalent can be measured in accordance with JIS K7236. In addition, for example, the hydroxyl equivalent can be calculated by dividing the molecular weight of KOH by the hydroxyl value measured in accordance with JIS K1557-1.
[0138] The glass transition temperature (Tg) of the component (D) is 20°C or lower, preferably 0°C or lower.
[0139] When (D) elastomer is contained, the content of (D) elastomer is not particularly limited. When the non-volatile components other than the (B) component in the resin composition are set to 100% by mass, from the viewpoint of further obtaining flexibility, it is preferably 10% by mass or more, more preferably 30% by mass or more, more preferably 40% by mass or more, and particularly preferably 50% by mass or more. From the viewpoint of significantly obtaining the desired effect of the present invention, the upper limit of the content of (D) elastomer is preferably 75% by mass or less, more preferably 70% by mass or less, more preferably 65% by mass or less, and particularly preferably 60% by mass or less.
[0140] <(E) Curing agent>
[0141] The resin composition of the present invention may contain (E) a curing agent as an optional component. By containing the (E) curing agent, the (A) epoxy resin can be easily cured.
[0142] As (E) curing agent, there is no particular limitation, as long as it has the function of curing epoxy resin, for example, phenol curing agent, naphthol curing agent, anhydride curing agent, active ester curing agent, benzoxazine curing agent, cyanate curing agent and carbodiimide curing agent can be cited. One curing agent can be used alone, or two or more can be used in combination. From the viewpoint of significantly obtaining the desired effect of the present invention, the (E) curing agent of the resin composition of the present invention is preferably selected from the group consisting of phenol curing agent, naphthol curing agent and active ester curing agent. In addition, in one embodiment, (E) curing agent preferably includes active ester curing agent.
[0143] As phenolic curing agents and naphthol curing agents, from the viewpoint of heat resistance and water resistance, phenolic curing agents with a novolac structure or naphthol curing agents with a novolac structure are preferred. In addition, from the viewpoint of adhesion to the adherend, nitrogen-containing phenolic curing agents or nitrogen-containing naphthol curing agents are preferred, and phenolic curing agents containing triazine skeletons or naphthol curing agents containing triazine skeletons are more preferred. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, phenolic novolac resins containing triazine skeletons are preferred. Specific examples of phenol-based curing agents and naphthol-based curing agents include "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Chemicals; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", "SN-375", "SN-48 ...375", "SN-375", "SN-375", "SN-3 "SN-395"; "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", "KA-1165" manufactured by DIC Corporation; "GDP-6115L", "GDP-6115H", "ELPC75" and other products manufactured by Qunrong Chemical Co., Ltd.
[0144] Examples of the acid anhydride curing agent include curing agents having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, dicarboxylic anhydride, and the like. Benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(trimellitic anhydride ester), styrene-maleic acid resin obtained by copolymerization of styrene and maleic acid, etc. Examples of commercially available acid anhydride curing agents include "HNA-100" and "MH-700" manufactured by Shin Nippon Rika Co., Ltd.
[0145] As active ester curing agent, there is no particular restriction, and usually preferably use phenolic esters, thiophenolic esters, N-hydroxylamine esters, esters of heterocyclic hydroxy compounds, etc., compounds having ester groups with more than 2 high reactive activities in 1 molecule. The active ester curing agent is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. In particular, from the viewpoint of improving heat resistance, the active ester curing agent preferably obtained by carboxylic acid compounds and hydroxy compounds, more preferably the active ester curing agent obtained by carboxylic acid compounds and phenolic compounds and / or naphthol compounds. As carboxylic acid compounds, for example benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be cited. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the so-called "dicyclopentadiene-type diphenol compound" refers to a diphenol compound obtained by condensing two molecules of phenol on one molecule of dicyclopentadiene.
[0146] Specifically, active ester compounds containing a dicyclopentadiene-type diphenol structure, active ester compounds containing a naphthalene structure, active ester compounds containing acetylated products of phenol novolac, and active ester compounds containing benzoylated products of phenol novolac are preferred, and active ester compounds containing a naphthalene structure and active ester compounds containing a dicyclopentadiene-type diphenol structure are more preferred. The so-called "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit composed of phenylene-dicyclopentalene-phenylene.
[0147] Examples of commercially available active ester curing agents include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000", "HPC-8000H", "HPC-8000-65T", "HPC-8000H-65TM", "EXB-8000L", and "EXB-8000L-65TM" (manufactured by DIC Corporation) as active ester compounds containing a dicyclopentadiene-type diphenol structure; and "EXB9416-70BK", "EXB-8150-65T" (manufactured by DIC Corporation) as active ester compounds containing a naphthalene structure. Co., Ltd.); "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound containing an acetylated product of phenol novolac; "YLH1026" (manufactured by Mitsubishi Chemical Corporation) as an active ester compound containing a benzoylated product of phenol novolac; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester curing agent of an acetylated product of phenol novolac; "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester curing agents of a benzoylated product of phenol novolac; and the like.
[0148] Specific examples of the benzoxazine-based curing agent include “JBZ-OP100D” and “ODA-BOZ” manufactured by JFE Chemical Co., Ltd.; “HFB2006M” manufactured by Showa High Molecular Co., Ltd.; and “Pd” and “Fa” manufactured by Shikoku Chemical Industry Co., Ltd.
[0149] Examples of the cyanate curing agent include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylene))benzene, bis(4-cyanatephenyl)sulfide, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers obtained by partially triazinizing these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" manufactured by Lonza Japan (both are phenol novolac-type multifunctional cyanate resins), "BA230", and "BA230S75" (prepolymers obtained by triazinizing part or all of bisphenol A dicyanate to form a trimer), etc.
[0150] Specific examples of the carbodiimide-based curing agent include "V-03" and "V-07" manufactured by Nisshinbo Chemical Co., Ltd.
[0151] When a curing agent is included, the amount ratio of the epoxy resin to the curing agent is preferably in the range of 1:0.2 to 1:2, more preferably 1:0.3 to 1:1.5, and further preferably 1:0.4 to 1:1.2, in terms of the ratio of [the total number of epoxy groups of the epoxy resin]: [the total number of reactive groups of the curing agent]. Here, the reactive group of the curing agent refers to an active hydroxyl group, an active ester group, etc., which varies depending on the type of curing agent. In addition, the so-called total number of epoxy groups of the epoxy resin refers to the value obtained by calculating the sum of the values obtained by dividing the non-volatile component mass of each epoxy resin by the epoxy equivalent for all epoxy resins, and the so-called total number of reactive groups of the curing agent refers to the value obtained by calculating the sum of the values obtained by dividing the non-volatile component mass of each curing agent by the reactive group equivalent for all curing agents. By making the amount ratio of the epoxy resin to the curing agent in the above range, the heat resistance of the obtained cured product is further improved.
[0152] When containing (E) curing agent, the content of (E) curing agent is not particularly limited. When the non-volatile components other than (B) component in the resin composition are set to 100% by mass, it is preferably 1% by mass or more, more preferably 5% by mass or more, further preferably 8% by mass or more, and particularly preferably 10% by mass or more. The upper limit of the content of (E) curing agent is preferably 40% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, and particularly preferably 15% by mass or less.
[0153] <(F) Curing accelerator>
[0154] The resin composition of the present invention may contain (F) a curing accelerator as an optional component. The (F) curing accelerator has a function of accelerating the curing of the (A) epoxy resin.
[0155] (F) curing accelerators include, for example, phosphorus curing accelerators, amine curing accelerators, imidazole curing accelerators, guanidine curing accelerators, and metal curing accelerators. Among them, phosphorus curing accelerators, amine curing accelerators, imidazole curing accelerators, and metal curing accelerators are preferred, and amine curing accelerators, imidazole curing accelerators, and metal curing accelerators are more preferred. One curing accelerator may be used alone, or two or more may be used in combination.
[0156] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate.
[0157] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine (DMAP), benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, and 4-dimethylaminopyridine is preferred.
[0158] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1' )]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline and other imidazole compounds, and adducts of imidazole compounds with epoxy resins.
[0159] As the imidazole-based curing accelerator, a commercially available item may be used, and examples thereof include "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0160] Examples of the guanidine-based curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine.
[0161] As metal curing accelerators, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. As specific examples of organic metal complexes, organic cobalt complexes such as cobalt acetylacetonate (II), cobalt acetylacetonate (III), organic copper complexes such as copper acetylacetonate (II), organic zinc complexes such as zinc acetylacetonate (II), organic iron complexes such as iron acetylacetonate (III), organic nickel complexes such as nickel acetylacetonate (II), and organic manganese complexes such as manganese acetylacetonate (II) can be cited. As organic metal salts, for example, zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.
[0162] When containing (F) curing accelerator, the content of (F) curing accelerator is not particularly limited. When the non-volatile components other than (B) component in the resin composition are set to 100% by mass, it is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, further preferably 0.05% by mass or more, and particularly preferably 0.1% by mass or more. The upper limit of the content of (F) curing accelerator is preferably 5% by mass or less, more preferably 2% by mass or less, further preferably 1% by mass or less, and particularly preferably 0.5% by mass or less.
[0163] <(G) Organic solvent>
[0164] The resin composition of the present invention may further contain (G) an organic solvent as an optional volatile component.
[0165] Examples of the organic solvent include ketone solvents such as acetone, methyl ethyl ketone, and cyclohexanone; ester solvents such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, carbitol acetate, diethylene glycol monoethyl ether acetate, and γ-butyrolactone; carbitol solvents such as cellosolve and butyl carbitol; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene; amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone; alcohol solvents such as methanol, ethanol, and 2-methoxypropanol; hydrocarbon solvents such as cyclohexane and methylcyclohexane, etc. The organic solvent may be used alone or in combination of two or more in any ratio.
[0166] <(H) Other additives>
[0167] For resin combination, except comprising above-mentioned composition, as arbitrary component, other additives can also be included.As such additive, for example organic filler, thickener, defoamer, leveler, adhesion imparting agent, polymerization initiator, flame retardant etc. can be enumerated.These additives can be used alone 1 kind, also can be used in combination of 2 or more kinds.Separate content can be suitably set by those skilled in the art.
[0168] <Method for producing resin composition>
[0169] In one embodiment, the resin composition of the present invention can be produced, for example, by the following method, which includes the following steps: (A) epoxy resin, (B) inorganic filler, (C) benzoxazine compound having one or more alicyclic structures in the molecule, (D) elastomer used as needed, (E) curing agent used as needed, (F) curing accelerator used as needed, (G) organic solvent used as needed, and (H) other additives used as needed are added to a reaction container in any order and / or partially or all at the same time and mixed to obtain a resin composition.
[0170] In the above-mentioned process, the temperature of the process of adding each component can be appropriately set, and heating and / or cooling can be performed temporarily or throughout the process of adding each component. In the process of adding each component, stirring or oscillation can be performed. In addition, after the above-mentioned process, it is preferred to further include the following process: using a stirring device such as a mixer, the resin composition is stirred to make it uniformly dispersed.
[0171] <Characteristics of resin composition>
[0172] The resin composition of the present invention contains (A) an epoxy resin, (B) an inorganic filler, and (C) a benzoxazine compound having one or more alicyclic structures in the molecule. Therefore, the elastic modulus of the cured product can be reduced, thereby achieving both suppression of warpage and excellent adhesion.
[0173] In one embodiment, from the viewpoint of relaxing the stress generated during thermal curing in order to reduce warping, the tensile modulus (GPa) of the cured product of the resin composition of the present invention at 23°C measured in accordance with JIS K7127 is preferably 15 GPa or less, more preferably 12 GPa or less, further preferably 11 GPa or less, and particularly preferably 10.5 GPa or less.
[0174] In one embodiment, the peeling intensity between the cured product of the resin composition of the present invention and the copper foil is preferably 0.25 kgf / cm or more, more preferably 0.3 kgf / cm or more, further preferably 0.35 kgf / cm or more, and particularly preferably 0.38 kgf / cm or more, when the load when peeling 35 mm in the vertical direction at a speed of 50 mm / min at room temperature is measured in accordance with JIS C6481.
[0175] In one embodiment, the warpage of a substrate formed by a resin composition layer of the present invention (thickness 100 μm) and a 12-inch silicon wafer when heat-treated at 180°C for 90 minutes can be preferably 4 mm or less, more preferably 3 mm or less, further preferably 2.5 mm or less, and particularly preferably 2.3 mm or less, 2.2 mm or less, 2.1 mm or less, or 2 mm or less.
[0176] <Application of resin composition>
[0177] The resin composition of the present invention can be suitably used as a resin composition for insulating purposes, especially as a resin composition for forming an insulating layer. Specifically, it can be suitably used as a resin composition for forming "the insulating layer for forming a conductor layer (the conductor layer is formed on the insulating layer, and the conductor layer includes a rewiring layer)" (a resin composition for forming an insulating layer for forming a conductor layer). In addition, in the printed wiring board described later, it can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (a resin composition for forming an insulating layer of a printed wiring board). The resin composition of the present invention can also be used for a wide range of uses that require a resin composition, such as resin sheets, sheet-like laminated materials such as prepregs, solder resists, bottom filling materials, chip bonding materials, semiconductor sealing materials, hole-filling resins, component embedding resins, etc.
[0178] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can also be suitably used as a resin composition for forming a "rewiring forming layer as an insulating layer for forming a rewiring layer" (resin composition for forming a rewiring forming layer) and a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When manufacturing a semiconductor chip package, a rewiring layer may be further formed on the sealing layer;
[0179] (1) a step of laminating a temporary fixing film on a substrate,
[0180] (2) a step of temporarily fixing the semiconductor chip on a temporary fixing film,
[0181] (3) a step of forming a sealing layer on a semiconductor chip,
[0182] (4) a step of peeling the substrate and the temporary fixing film from the semiconductor chip,
[0183] (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off, and
[0184] (6) A step of forming a rewiring layer as a conductor layer on the rewiring formation layer.
[0185] Furthermore, the resin composition of the present invention forms an insulating layer having good component embedding properties, and therefore can be suitably used also when the printed wiring board is a component-embedded wiring board.
[0186] <Sheet-shaped laminated materials>
[0187] The resin composition of the present invention may be used by coating in a varnish state, but is usually preferably used in the form of a sheet-like laminate containing the resin composition in industrial terms.
[0188] As the sheet-like laminated material, the following resin sheets and prepregs are preferred.
[0189] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support, and the resin composition layer is formed of the resin composition of the present invention.
[0190] From the viewpoint of thinning the printed wiring board and providing a cured product having excellent insulation properties even if the cured product of the resin composition is a thin film, the thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be 5 μm or more, 10 μm or more, etc.
[0191] Examples of the support include films made of plastic materials, metal foils, and release papers, and films made of plastic materials and metal foils are preferred.
[0192] When a film formed of a plastic material is used as a support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"), polycarbonate (hereinafter sometimes referred to as "PC"), acrylic polymers such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0193] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. The copper foil may be a foil made of a single metal such as copper or an alloy of copper and other metals (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0194] The surface of the support that contacts the resin composition layer may be subjected to matte treatment, corona treatment, or antistatic treatment.
[0195] In addition, as a support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As a release agent for the release layer of the support with a release layer, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, polyurethane resins, and silicone resins can be cited. The support with a release layer can use commercial products, for example, as a PET film having a release layer with an alkyd resin-based release agent as the main component, Lintec's "SK-1", "AL-5", "AL-7", Toray's "Lumirror T60", Teijin's "Purex", UNITIKA's "Unipeel" and the like can be cited.
[0196] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.
[0197] In one embodiment, the resin sheet may further include an arbitrary layer as required. As the arbitrary layer, for example, a protective film selected according to the support body and disposed on the surface of the resin composition layer that is not bonded to the support body (i.e., the surface on the opposite side of the support body) can be cited. The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, dust and the like can be prevented from adhering to the surface of the resin composition layer or from being damaged on the surface of the resin composition layer.
[0198] The resin sheet can be produced, for example, by directly applying a liquid resin composition to a support using a die coater or the like, or by preparing a resin varnish by dissolving the resin composition in an organic solvent and applying the resin varnish to a support using a die coater or the like, and then drying it to form a resin composition layer.
[0199] Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone (MEK), and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; amide solvents such as dimethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone, etc. The organic solvent may be used alone or in combination of two or more.
[0200] Drying can be carried out by known methods such as heating and blowing hot air. The drying conditions are not particularly limited, and the drying is carried out in a manner such that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. The drying conditions vary with the boiling point of the organic solvent in the resin varnish. For example, when a resin varnish containing 30% to 60% by mass of an organic solvent is used, the resin composition layer can be formed by drying at 50° C. to 150° C. for 3 minutes to 10 minutes.
[0201] The resin sheet can be stored by winding it into a roll. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0202] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber base material with the resin composition of the present invention.
[0203] The sheet-like fiber substrate used in the prepreg is not particularly limited, and glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, etc. can be used as materials commonly used as prepreg substrates. From the viewpoint of thinning the printed wiring board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.
[0204] The prepreg can be produced by a known method such as a hot melt method or a solvent method.
[0205] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.
[0206] In the present invention using a resin composition containing a combination of the components (A), (B) and (C) in specific amounts, a sheet-like laminate material that is very useful in the manufacture of a printed wiring board can be obtained, which provides a cured product having a high glass transition temperature, a low dielectric loss tangent and good adhesion to a conductor layer.
[0207] The sheet-like laminated material of the present invention can be suitably used to form an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be more suitably used to form an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board).
[0208] <Printed wiring board>
[0209] The printed wiring board of the present invention includes an insulating layer formed of a cured product obtained by curing the resin composition of the present invention.
[0210] The printed wiring board can be produced, for example, using the above-mentioned resin sheet by a method including the following steps (I) and (II);
[0211] (I) a step of laminating a resin sheet on the inner substrate so that the resin composition layer of the resin sheet is bonded to the inner substrate,
[0212] (II) A step of curing (for example, thermally curing) the resin composition layer to form an insulating layer.
[0213] The "inner substrate" used in step (I) refers to a member that becomes a substrate of a printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, a thermosetting polyphenylene ether substrate, and the like. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may be patterned. An inner substrate having a conductor layer (circuit) formed on one or both sides of a substrate is sometimes referred to as an "inner circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed when manufacturing a printed wiring board is also included in the so-called "inner substrate" in the present invention. When the printed wiring board is a circuit board with built-in components, an inner substrate with built-in components can be used.
[0214] The lamination of the inner substrate and the resin sheet can be performed, for example, by heat-pressing the resin sheet to the inner substrate from the support body side. As a component for heat-pressing the resin sheet to the inner substrate (hereinafter also referred to as a "heat-pressing component"), for example, a heated metal plate (SUS end plate, etc.) or a metal roller (SUS roller) can be cited. It should be noted that it is preferred that the heat-pressing component is not directly pressed against the resin sheet, but is pressed through an elastic material such as heat-resistant rubber so that the resin sheet fully follows the surface unevenness of the inner substrate.
[0215] The lamination of the inner substrate and the resin sheet can be implemented by vacuum lamination. In the vacuum lamination method, the heating and pressing temperature is preferably 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heating and pressing pressure is preferably 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the heating and pressing time is preferably 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably implemented under reduced pressure conditions with a pressure of 26.7hPa or less.
[0216] Lamination can be performed by a commercially available vacuum laminator. Examples of the commercially available vacuum laminator include a vacuum pressure laminator manufactured by Meiki Mfg. Co., Ltd., a vacuum applicator manufactured by Nikko-Materials Co., Ltd., and a batch vacuum pressure laminator.
[0217] After lamination, at normal pressure (atmospheric pressure), for example, the heating and pressing member is pressed from the support body side, thereby, the laminated resin sheet can be smoothed. The pressing conditions for the smoothing treatment can be set to the same conditions as the above-mentioned heating and pressing conditions for the lamination. The smoothing treatment can be carried out by a commercially available laminator. It should be noted that the lamination and smoothing treatment can be carried out continuously using the above-mentioned commercially available vacuum laminator.
[0218] The support may be removed between step (I) and step (II), or may be removed after step (II).
[0219] In step (II), the resin composition layer is cured (eg, thermally cured) to form an insulating layer composed of a cured product of the resin composition. The curing conditions of the resin composition layer are not particularly limited, and conditions commonly used in forming an insulating layer of a printed wiring board can be used.
[0220] For example, the heat curing conditions of the resin composition layer vary depending on the type of the resin composition, and the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and further preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and further preferably 15 minutes to 100 minutes.
[0221] The resin composition layer may be preheated at a temperature lower than the curing temperature before the resin composition layer is thermally cured. For example, before the resin composition layer is thermally cured, the resin composition layer is preheated at a temperature of 50° C. or higher and lower than 120° C., preferably 60° C. or higher and lower than 115° C., more preferably 70° C. or higher and lower than 110° C., for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and further preferably 15 minutes to 100 minutes.
[0222] When manufacturing a printed wiring board, the step (III) of opening a hole in the insulating layer, the step (IV) of roughening the insulating layer, and the step (V) of forming a conductor layer can be further implemented. The above-mentioned steps (III) to (V) can be implemented according to various methods known to those skilled in the art that can be used in the manufacture of a printed wiring board. It should be noted that when the support body is removed after step (II), the removal of the support body can be implemented between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, as needed, the formation of the insulating layer and the conductor layer of steps (II) to (V) can be repeatedly implemented to form a multilayer wiring board.
[0223] In other embodiments, the printed wiring board of the present invention can be produced using the above-mentioned prepreg. The production method is basically the same as that in the case of using a resin sheet.
[0224] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as through holes and through holes in the insulating layer. Step (III) can be implemented using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used in forming the insulating layer. The size and shape of the hole can be appropriately determined according to the design of the printed wiring board.
[0225] Step (IV) is a step of roughening the insulating layer. Usually, in step (IV), smear removal is also performed. The steps and conditions of the roughening treatment are not particularly limited, and the known steps and conditions commonly used when forming the insulating layer of the printed wiring board can be adopted. For example, the insulating layer can be roughened by sequentially implementing a swelling treatment based on a swelling solution, a roughening treatment based on an oxidant, and a neutralization treatment based on a neutralizing solution.
[0226] There is no particular limitation on the swelling liquid used in the roughening treatment, and examples thereof include alkaline solutions, surfactant solutions, and the like. Alkaline solutions are preferred, and sodium hydroxide solutions and potassium hydroxide solutions are more preferred as the alkaline solutions. Examples of commercially available swelling liquids include "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan. There are no particular limitations on the swelling treatment based on the swelling liquid, and for example, it can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred that the insulating layer be immersed in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.
[0227] There are no particular restrictions on the oxidizing agent used in the roughening treatment, and examples thereof include alkaline permanganate solutions formed by dissolving potassium permanganate or sodium permanganate in an aqueous solution of sodium hydroxide. The roughening treatment based on an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. As commercially available oxidizing agents, alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securiganth P" manufactured by Atotech Japan Co., Ltd. can be cited.
[0228] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and examples of commercially available products include "Reduction Solution Securiganth P" manufactured by Atotech Japan Co., Ltd.
[0229] The treatment with the neutralizing solution can be performed by immersing the treated surface after the roughening treatment with the oxidizing agent in the neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. In view of operability, etc., it is preferable to immerse the object after the roughening treatment with the oxidizing agent in the neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes.
[0230] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment is not particularly limited, preferably 500nm or less, more preferably 400nm or less, and further preferably 300nm or less. There is no particular restriction on the lower limit, and it may be preferably 0.5nm or more, and more preferably 1nm or more. In addition, the root mean square roughness (Rq) of the insulating layer surface after roughening treatment is preferably 500nm or less, more preferably 400nm or less, and further preferably 300nm or less. There is no particular restriction on the lower limit, and it may be preferably 0.5nm or more, and more preferably 1nm or more. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.
[0231] Step (V) is a step of forming a conductor layer, and a conductor layer is formed on the insulating layer. The conductor material used in the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer can be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above group (for example, nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy) can be cited. Among them, from the viewpoint of versatility, cost, ease of patterning, etc. of the formation of the conductor layer, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is further preferred.
[0232] The conductor layer may be a single-layer structure, or a multilayer structure in which two or more single metal layers or alloy layers formed of different types of metals or alloys are stacked. When the conductor layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.
[0233] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is usually 3 μm to 35 μm, preferably 5 μm to 30 μm.
[0234] In one embodiment, the conductor layer can be formed by plating. For example, the surface of the insulating layer can be plated using a known technique such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. From the perspective of manufacturing simplicity, it is preferably formed using a semi-additive method. An example of forming a conductor layer using a semi-additive method is shown below.
[0235] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. A metal layer is formed on the exposed plating seed layer by electrolytic plating, and then the mask pattern is removed. Then, the unnecessary plating seed layer is removed by etching or the like, and a conductor layer having a desired wiring pattern can be formed.
[0236] In other embodiments, the conductor layer can be formed using a metal foil. When a metal foil is used to form a conductor layer, step (V) is preferably implemented between step (I) and step (II). For example, after step (I), the support is removed and a metal foil is laminated on the surface of the exposed resin composition layer. The lamination of the resin composition layer and the metal foil can be implemented using a vacuum lamination method. The lamination conditions can be the same as those described for step (I). Next, step (II) is implemented to form an insulating layer. Then, using the metal foil on the insulating layer, a conductor layer with a desired wiring pattern can be formed using existing known techniques such as a subtractive method and an improved semi-additive method.
[0237] The metal foil can be produced by a known method such as electrolysis or rolling. Commercially available metal foils include HLP foil and JXUT-III foil manufactured by JX Nippon Mining & Metals Co., Ltd., and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Co., Ltd.
[0238] When a printed wiring board is produced using the resin composition of the present invention containing a combination of the components (A), (B) and (C) in specific amounts, the adhesion between the conductor layer and the insulating layer can be significantly improved regardless of whether the conductor layer is formed by plating or using a metal foil.
[0239] <Semiconductor devices>
[0240] The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be produced using the printed wiring board of the present invention.
[0241] Examples of the semiconductor device include various semiconductor devices used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and airplanes). Example
[0242] The present invention is specifically described below by way of examples. The present invention is not limited to these examples. It should be noted that, below, unless otherwise clearly stated, "parts" and "%" indicating amounts represent "parts by mass" and "% by mass", respectively.
[0243] <Synthesis Example 1: Synthesis of bis[4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)cyclohexyl]methane>
[0244] [Chemical formula 4]
[0245] .
[0246] 4,4'-methylenebis(cyclohexylamine), phenol and 92% paraformaldehyde were heated to reflux in toluene at a molar ratio of 1:2:4.1, respectively, to react. After toluene was distilled off, the target compound was obtained. In the purity measurement by GPC, the purity as a monomer was 65%. Although a polymer was included as a by-product, it was used directly in the examples.
[0247] <Synthesis Example 2: Synthesis of 1,4-bis(3,4-dihydro-2H-1,3-benzoxazin-3-yl)cyclohexane>
[0248] [Chemical formula 5]
[0249] .
[0250] 1,4-cyclohexanediamine, phenol and 92% paraformaldehyde were heated to reflux in toluene at a molar ratio of 1:2:4.1, respectively, to react. After toluene was distilled off, the target compound was obtained. In the purity measurement by GPC, the purity as a monomer was 60%. Although a polymer was included as a by-product, it was used directly in the examples.
[0251] <Synthesis Example 3: Synthesis of elastomer>
[0252] In a reaction container, 69 g of a difunctional hydroxyl-terminated polybutadiene ("G-3000" manufactured by Nippon Soda Co., Ltd., number average molecular weight = 3000, hydroxyl equivalent = 1800 g / eq.), 40 g of an aromatic hydrocarbon mixed solvent ("Ipzole 150" manufactured by Idemitsu Petrochemical Co., Ltd.), and 0.005 g of dibutyltin laurate were placed and mixed to be uniformly dissolved. After becoming uniform, the temperature was raised to 60° C., and 8 g of isophorone diisocyanate ("IPDI" manufactured by Evonik Degussa Japan Co., Ltd., isocyanate equivalent = 113 g / eq.) was added while stirring, and the reaction was carried out for about 3 hours.
[0253] Next, 23 g of cresol novolac resin ("KA-1160" manufactured by DIC Corporation, hydroxyl equivalent = 117 g / eq.) and 60 g of diethylene glycol monoethyl ether acetate (manufactured by Daicel Corporation) were added to the reaction product, and the temperature was raised to 150° C. while stirring, and the reaction was carried out for about 10 hours. FT-IR was used to analyze the reaction product at 2250 cm -1 The disappearance of the NCO peak was confirmed. The time point when the disappearance of the NCO peak was confirmed was regarded as the end point of the reaction, and the reactants were cooled to room temperature. Then, the reactants were filtered with a 100-mesh filter cloth to obtain an elastomer having a butadiene structure and phenolic hydroxyl groups (butadiene resin containing phenolic hydroxyl groups: non-volatile components 50% by mass). The number average molecular weight of the elastomer is 5900, and the glass transition temperature is -7°C.
[0254] <Example 1>
[0255] 5 parts of a biphenyl epoxy resin ("NC3000" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of 276 g / eq.), 2 parts of a bisphenol epoxy resin ("ZX1059" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., a 1:1 mixture of bisphenol A and bisphenol F, epoxy equivalent of 169 g / eq.), 0.5% by mass of spherical silica ("SO- C2", with an average particle size of 0.5 μm), 70 parts of propylene glycol (C2", with an average particle size of 0.5 μm), 30 parts of the elastomer obtained in Synthesis Example 3, 2 parts of the benzoxazine compound obtained in Synthesis Example 1, 3 parts of cresol novolac resin ("KA-1160" manufactured by DIC Corporation, phenolic hydroxyl equivalent: 117 g / eq), 0.1 parts of a curing accelerator ("1B2PZ" manufactured by Shikoku Chemicals Co., Ltd., 1-benzyl-2-phenylimidazole), and 15 parts of methyl ethyl ketone are mixed and uniformly dispersed using a high-speed rotating mixer to prepare a resin composition.
[0256] <Example 2>
[0257] A resin composition was prepared in the same manner as in Example 1 except that 2 parts of the benzoxazine compound obtained in Synthesis Example 2 was used instead of 2 parts of the benzoxazine compound obtained in Synthesis Example 1.
[0258] <Example 3>
[0259] A resin composition was prepared in the same manner as in Example 1, except that 115 parts of spherical alumina (DAW-03 manufactured by DENKA Corporation, with an average particle size of 3.7 μm) was used, which was surface-treated with 0.5 mass% of an amine-based alkoxysilane compound (“KBM573” manufactured by Shin-Etsu Chemical Co., Ltd.) instead of 70 parts of spherical silica (“SO-C2” manufactured by Yaduma Co., Ltd., with an average particle size of 0.5 μm).
[0260] <Example 4>
[0261] Instead of 70 parts of spherical silica (SO-C2 manufactured by Yaduma Co., Ltd., with an average particle size of 0.5 μm) surface-treated with 0.5% by mass of an amine-based alkoxysilane compound (KBM573 manufactured by Shin-Etsu Chemical Co., Ltd.), spherical alumina (with an average particle size of 1.5 μm and a specific surface area of 2.0 m2) surface-treated with 0.5% by mass of an amine-based alkoxysilane compound (KBM573 manufactured by Shin-Etsu Chemical Co., Ltd.) was used. 2 / g, and a maximum particle size of 5 μm) was 115 parts, and a resin composition was prepared in the same manner as in Example 1.
[0262] <Comparative Example 1>
[0263] A resin composition was prepared in the same manner as in Example 1 except that 2 parts of the benzoxazine compound obtained in Synthesis Example 1 was not used and the amount of cresol novolac resin ("KA-1160" manufactured by DIC Corporation, phenolic hydroxyl equivalent: 117 g / eq) used was changed from 3 parts to 5 parts.
[0264] <Comparative Example 2>
[0265] A resin composition was prepared in the same manner as in Example 1, except that 2 parts of a commercially available benzoxazine compound ("Pd-type benzoxazine", bis[4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane manufactured by Shikoku Chemical Industry Co., Ltd.) was used instead of 2 parts of the benzoxazine compound obtained in Synthesis Example 1.
[0266] <Test Example 1: Measurement and Evaluation of Tensile Elastic Modulus>
[0267] A glass cloth-based epoxy resin double-sided copper-clad laminate ("R5715ES" manufactured by Panasonic Corporation, with a thickness of 0.7 mm and a square of 255 mm) was overlapped on the release agent-untreated surface of a release agent-treated PET film ("501010" manufactured by Lintec Corporation, with a thickness of 38 μm and a square of 240 mm), and the four sides were fixed with polyimide tape (with a width of 10 mm) (hereinafter sometimes referred to as "fixed PET film").
[0268] The resin composition prepared in the examples and comparative examples is applied to the demolding surface of the above-mentioned "fixed PET film" using a die coater in such a manner that the thickness of the dried resin composition layer becomes 50 μm, and dried at 80°C to 120°C (average 100°C) for 6 minutes to obtain a resin sheet. Next, it is placed in an oven at 180°C, and then the resin composition layer is thermally cured under curing conditions for 90 minutes. After thermal curing, the polyimide tape is peeled off, and the cured product is removed from the glass cloth substrate epoxy resin double-sided copper-clad laminate, and the PET film ("501010" manufactured by Lintec Corporation) is also peeled off to obtain a sheet-like cured product. The obtained cured product is referred to as the "cured product for evaluation".
[0269] The cured product for evaluation was cut into a dumbbell-shaped No. 1 shape to obtain a test piece. For the test piece, a tensile strength measurement was performed using a tensile testing machine "RTC-1250A" manufactured by Orientec, and the elastic modulus at 23°C was obtained. The measurement was carried out in accordance with JISK7127. This operation was performed 3 times, and the average value is shown in the table below. In order to reduce warping and considering the stress relaxation generated during thermal curing, it is preferred that the tensile modulus is low. In view of this, the case where the tensile modulus is less than 10.5GPa is evaluated as "0", and the case where the tensile modulus is greater than 10.5GPa is evaluated as "×".
[0270] <Test Example 2: Measurement and Evaluation of Peel Strength>
[0271] As the inner layer substrate, a glass cloth-based epoxy resin double-sided copper-clad laminate with copper foil on the surface was prepared (the copper foil thickness was 18 μm, the substrate thickness was 0.8 mm, "R1515A" manufactured by Panasonic Corporation). The copper foil on the surface of the inner layer substrate was completely etched away. Then, it was dried at 190° C. for 30 minutes.
[0272] An intermittent vacuum pressurized laminator (Nikko Materials Co., Ltd. 2-stage layer-adding laminator "CVP700") is used to laminate the resin composition obtained in the above-mentioned embodiments and comparative examples on both sides of the inner substrate in such a way that the resin composition layer is bonded to the aforementioned inner substrate. The lamination is implemented in the following manner: decompression is performed for 30 seconds to make the air pressure below 13hPa, and then, crimping is performed for 30 seconds at a temperature of 100°C and a pressure of 0.74MPa. Next, at atmospheric pressure, the laminated resin sheet is hot-pressed for 60 seconds at a pressure of 0.5MPa at 100°C to smooth it. Then, the support is peeled off to obtain an "intermediate multilayer body I" comprising a resin composition layer, an inner substrate and a resin composition layer in sequence.
[0273] On the other hand, a copper foil having a glossy surface (thickness 35 μm, "3EC-III" manufactured by Mitsui Metals Co., Ltd.) was prepared. The glossy surface of the copper foil was etched with a copper etching amount of 1 μm using a microetchant ("CZ8101" manufactured by MEC Corporation) to perform a roughening treatment. The copper foil obtained in the above manner is referred to as "roughened copper foil".
[0274] The roughened copper foil is laminated on both sides of the intermediate multilayer body I in such a manner that the surface of the roughened copper foil is bonded to the resin composition layer of the intermediate multilayer body I. The lamination is performed under the same conditions as the lamination of the resin sheet to the inner substrate. Thus, an "intermediate multilayer body II" containing a roughened copper foil, a resin composition layer, an inner substrate, a resin composition layer and a roughened copper foil is obtained in this order.
[0275] The intermediate multilayer body II was placed in an oven at 180°C and heated for an additional 90 minutes. Thus, the resin composition layer was thermally cured to obtain an "evaluation substrate" sequentially comprising a roughened copper foil, an insulating layer as a cured product of the resin composition layer, an inner substrate, an insulating layer as a cured product of the resin composition layer, and a roughened copper foil. In the evaluation substrate, the roughened copper foil is equivalent to the conductor layer.
[0276] Using the aforementioned evaluation substrate, the peel strength between the roughened copper foil and the insulating layer was measured. The peel strength was measured in accordance with JIS C6481. Specifically, the peel strength was measured by the following operation. On the roughened copper foil of the evaluation substrate, a cut was formed to surround a rectangular portion with a width of 10 mm and a length of 100 mm. One end of the rectangular portion was peeled off and clamped with a clamp (manufactured by TSE, AUTO COM type testing machine "AC-50C-SL"). The aforementioned rectangular portion was peeled off in the vertical direction within a range of 35 mm in length, and the load (kgf / cm) during the peeling was measured as the peel strength. The aforementioned peeling was performed at room temperature at a speed of 50 mm / min. The case where the peel strength was 0.39 kgf / cm or more was evaluated as "○", and the case where the peel strength was less than 0.39 kgf / cm was evaluated as "×".
[0277] <Test Example 3: Evaluation of Warpage>
[0278] As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) having a release layer was prepared. The resin composition obtained in the above-mentioned Examples and Comparative Examples was uniformly applied on the release layer of the support so that the thickness of the resin composition layer after drying was 50 μm. Then, the resin varnish was dried at 80°C to 120°C (average 100°C) for 6 minutes to obtain a resin sheet including a support and a resin composition layer.
[0279] Next, the above-mentioned resin sheet is laminated with a thickness of 50 μm on the entire single side of a 12-inch silicon wafer (thickness of 775 μm) using an intermittent vacuum pressure laminator (Nikko Materials Co., Ltd. 2-stage build-up laminator "CVP700"), thereby performing two-layer lamination to form a resin composition layer with a thickness of 100 μm. In an oven, the obtained silicon wafer with a resin composition layer is heat-treated at 180°C and 90 minutes to form a silicon wafer with a cured resin composition layer (i.e., an insulating layer). The end of the obtained wafer with an insulating layer is pressed on a stage, and the distance between the end of the wafer on the opposite side of the pressed position and the stage is measured as the amount of warping. The case where the amount of warping is 0 to 2 mm is evaluated as "○", and the case where the amount of warping is greater than 2 mm is evaluated as "×".
[0280] The nonvolatile components of the resin compositions of Examples and Comparative Examples and the amounts used thereof, and the evaluation results of the Test Examples are shown in Table 1 below.
[0281] [Table 1]
[0282] .
[0283] From the above results, it is understood that when (C) a benzoxazine compound having one or more alicyclic structures in the molecule is used, both suppression of warpage and excellent adhesion can be achieved.
Claims
1. A resin composition comprising: (A) an epoxy resin, (B) an inorganic filler, and (C) a benzoxazine compound having an alicyclic structure in the molecule, Component (C) is a compound represented by formula (2), In the formula, R 1 and R 2 Each independently represents a substituent, Y represents a chemical bond, an alkylene group having 1 to 6 carbon atoms, -O-, -S-, -SO2-, -NH-, -CO-, -CONH-, -NHCO-, -COO- or -OCO-, s and t each independently represent an integer of 0 to 4, u represents 0 or 1, When the nonvolatile components other than the component (B) in the resin composition are set to 100% by mass, the content of the component (A) is 5% by mass or more and 60% by mass or less, When all nonvolatile components in the resin composition are taken as 100% by mass, the content of the component (B) is 30% by mass or more. When the nonvolatile matter other than the (B) component in the resin composition is 100 mass %, the content of the (C) component is 0.1 mass % or more and 30 mass % or less.
2. The resin composition according to claim 1, wherein When the nonvolatile matter other than the component (B) in the resin composition is taken as 100% by mass, the content of the component (A) is 20% by mass or more and 30% by mass or less.
3. The resin composition according to claim 1, wherein When all nonvolatile components in the resin composition are taken as 100% by mass, the content of the component (B) is 50% by mass or more.
4. The resin composition according to claim 1, wherein When all nonvolatile components in the resin composition are taken as 100% by mass, the content of the component (B) is 70% by mass or more.
5. The resin composition according to claim 1, wherein When all nonvolatile components in the resin composition are taken as 100% by mass, the content of the component (B) is 98% by mass or less.
6. The resin composition according to claim 1, wherein When all nonvolatile components in the resin composition are taken as 100% by mass, the content of the component (B) is 85% by mass or less.
7. The resin composition according to claim 1, wherein The average particle size of the component (B) is 40 μm or less.
8. The resin composition according to claim 1, wherein The average particle size of the component (B) is 10 μm or less.
9. The resin composition according to claim 1, wherein The average particle size of the component (B) is 5 μm or less.
10. The resin composition according to claim 1, wherein The average particle size of the component (B) is 0.01 μm or more.
11. The resin composition according to claim 1, wherein The average particle size of the component (B) is 0.4 μm or more.
12. The resin composition according to claim 1, wherein When the nonvolatile matter other than the (B) component in the resin composition is 100% by mass, the content of the (C) component is 5% by mass or more and 8% by mass or less. 13 . The resin composition according to claim 1 , further comprising (D) an elastomer.
14. The resin composition according to claim 13, wherein When the nonvolatile matter other than the (B) component in the resin composition is 100 mass %, the content of the (D) component is 10 mass % or more and 75 mass % or less.
15. The resin composition according to claim 13, wherein When the nonvolatile matter other than the (B) component in the resin composition is 100 mass %, the content of the (D) component is 50 mass % or more and 60 mass % or less. 16 . The resin composition according to claim 1 , further comprising (E) a curing agent.
17. The resin composition according to claim 16, wherein When the nonvolatile matter other than the (B) component in the resin composition is 100 mass %, the content of the (E) component is 1 mass % or more and 40 mass % or less.
18. The resin composition according to claim 16, wherein When the nonvolatile matter other than the (B) component in the resin composition is 100% by mass, the content of the (E) component is 10% by mass or more and 15% by mass or less. 19 . The resin composition according to claim 1 , further comprising (F) a curing accelerator.
20. The resin composition according to claim 19, wherein When the nonvolatile matter other than the (B) component in the resin composition is 100 mass %, the content of the (F) component is 0.001 mass % or more and 5 mass % or less.
21. The resin composition according to claim 19, wherein When the nonvolatile matter other than the (B) component in the resin composition is 100 mass %, the content of the (F) component is 0.1 mass % or more and 0.5 mass % or less.
22. The resin composition according to claim 1, which is used for forming an insulating layer. 23 . A cured product, which is a cured product of the resin composition according to claim 1 . 24 . A sheet-like laminated material comprising the resin composition according to claim 1 . 25 . A resin sheet comprising: a support; and a resin composition layer formed from the resin composition according to claim 1 and provided on the support. 26 . A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to claim 1 .
27. A semiconductor device comprising the printed wiring board according to claim 26.
Citation Information
Patent Citations
Thermosetting resin composition containing modified polyimide resin
JP2006037083A
Resin composition
JP2016027097A
Resin composition for interlayer insulation of multilayer printed wiring board
WO2008153208A1
Resin composition for printed wiring board
WO2010053185A1
Heat-curable resin composition
WO2016129541A1